1027. Long-Term Efficacy, Safety, and Durability of Ibalizumab-Based Regimens in Subgroup of TMB-202 Participants. (31st December 2020) - Towner, William; DeJesus, Edwin; Schrader, Shannon; De Vente, Jerome; McGary, Colleen; Zogheib, Mohammed; Weinheimer, Steven; Mesquita, Pedro
Abstract: Background: Third line antiretroviral regimens have been associated with suboptimal virologic suppression, due to drug cross-resistance and regimen complexity. Yet, in treatment-experienced (TE) HIV patients, ART durability is essential for preventing further resistance and decreasing HIV-associated morbidity and mortality. Ibalizumab (IBA), the first long-acting, post-attachment inhibitor approved to treat multi-drug resistant (MDR) HIV, may support regimen durability given its directly observed administration. We analyzed the safety, efficacy, and durability of response in 12 patients who started IBA in a Phase 2b study. Methods: In TMB-202, 113 patients with MDR HIV received either 2000 mg IBA every 4 weeks (n=54) or 800 mg IBA every 2 weeks (n=59) for 24 weeks with an optimized background regimen (OBR). Of 96 patients who completed TMB-202, 56 transferred into an investigator-sponsored investigational new drug protocol and 12 later moved onto an expanded access protocol, TMB-311, where efficacy and safety were monitored until IBA was commercially available (approval 2018). Results: Baseline median viral load (VL) and CD4 count for the 12 patients were 4.4 log10 copies/mL (c/mL) and 135 cells/mL, respectively. The median duration of HIV infection was 22 years (range 18-25). At the completion of TMB-202 11/12 achieved virologic suppression (VL < 200 c/mL) and 8/12 had VL < 50 c/mL. All 12 patients were suppressed (VL < 50 c/mL) at their last TMB-311 visit. Patients gained an average of 99 CD4 cells/mL relative to baseline. There were no treatment-emergent adverse events (TEAE) or therapy discontinuations related to IBA during follow-up. Two patients died from unrelated causes. Overall, the 12 patients remained on IBA for an average of 8.9 years (range 8-9.5), during which 8/12 did not require addition of new ARVs to their OBR to maintain suppression. Figure 1: duration of ibalizumab-based regimen is displayed for the 12 patients. Grey bars represent patients with no addition of new ARVs to OBR. Black bars represent patients with an addition to OBR. Asterisks represent addition of ritonavir only. Conclusion: Data from 12 patients who received IBA for an average of 9 years validate the long-term efficacy and safety of IBA in TE patients. Importantly, for most patients, the durability of virologic response was maintained with minimal adjustments to the OBR. Altogether, these data demonstrate the contribution of IBA towards durable viral suppression in TE HIV patients with limited therapeutic options. Disclosures: William Towner, MD, Dynavax (Research Grant or Support)Gilead (Grant/Research Support)Merck (Research Grant or Support)Tai Med (Research Grant or Support)ViiV (Research Grant or Support) Edwin DeJesus, MD, Gilead Sciences (Advisor or Review Panel member) Colleen McGary, PhD, Theratechnologies (Employee) Mohammed Zogheib, PharmD, MPH, Theratechnologies (Employee) Steven Weinheimer, PhD, TaiMed Biologics USA (Employee) Pedro Mesquita, PhD, Theratechnologies, Inc. (Employee)